Analysis of Spelling Errors in Official Letters by Grade VII Students of SMP Negeri 24 Padang - Gita Puspita Sari; Azzurra Azahri; Ananda Bunga Maysuri; Suraiya; Reska Syofyani Putri (Raja Zulkarnain Education Foundation, 2026)
This study aims to analyze errors in the use of capital letters and punctuation marks in official letters written by students. The focus of the study is on the forms, types, and frequency of spelling errors that appear in official letters as a type of formal text requiring linguistic accuracy. This research employed a qualitative descriptive method with documentation as the data collection technique. The data consisted of official letters written by students, obtained from the Indonesian language teacher. The data were then analyzed using content analysis techniques by identifying, classifying, and calculating errors in the use of capital letters and punctuation based on the rules of Indonesian Spelling (Ejaan Bahasa Indonesia). The results showed that there were 155 errors in the use of capital letters out of a total of 894 data points, accounting for 17.34%. In addition, 52 punctuation errors were found, representing 6.01% of the total data. The most dominant errors occurred in the writing of place names, the use of formal forms of address, and the formatting of letterheads. These findings indicate that students have not yet fully understood or applied the rules of Indonesian spelling in writing official letters. Therefore, continuous practice, habituation, and greater emphasis on spelling instruction in official letter writing activities are necessary to improve students’ written language skills, particularly in the accurate use of capital letters and punctuation marks.